(untitled) (Research, Society and Development, 2023)
Guided by the questioning about how issues related to animals are addressed in research aimed at teaching chemistry, we conducted a review in international journals in science, chemistry, education and animal ethics, seeking to identify a possible dialogue between the themes. Highlighting the novelty of these possible relations, the objective was to assemble a panoramic impression of it, assuming that inserting the animal theme in chemistry classes would improve learning, the development of values generally associated with a critical citizen, and would promote significant practices linked to the questioning of reality. In line with the themes of the works found, we built a theoretical basis on the issue between animal consumption and the future of the environment, followed by the methodology and analysis of the selected articles, divided into three categories: environmental chemistry as driving issue to construct scientific concepts, discussions on food and nutrition through a scientific view, and introduction of concepts, analysis and methods through food chemistry. The analyzed texts brought several aspects of the investigated relations, dealing with both food health and environmental problems. Along with that, they explored numerous pedagogical possibilities in order to raise awareness and make the teaching-learning process more attractive and effective. Among the conclusions, there is that animal ethics, through its various aspects, is either not contemplated or appears in a veiled way by publications in the area of chemistry education. We recognize that there is a long way to go in search of a new perception.